International Relations in the Czech Republic: Where Have All the Women Gone? - Nyklová, Blanka; Cidlinská, Kateřina; Fárová, Nina (Czech Journal of International Relations, 2019)
In this article, we strive to explore what are some of the causes of the scarcity of women researchers in Czech international relations in comparison to the representation of women students in the field. To answer this question, we analysed a set of semi-structured interviews with international relations students and accessible syllabi using the conceptual framework of Sandra Harding´ s gendered universe, which differentiates between the operations of gender on the individual, structural and symbolic level. We identified some gendered barriers that might be blocking women researchers´ access to the field. On this basis we suggest that the lack of women researchers in the field parallels the situation in other social sciences and humanities disciplines, but the situation in international relations is further exacerbated by the local circumstances of the foundation of the discipline, which shaped it as a predominantly masculine field with a specific gender-blind version of doing research and academic careers.